Zur Frage über das Restglied im Zentralen Grenzwertsatz - Survila, P. (Lithuanian Mathematical Journal, 1962)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:П. Сурвила, К вопросу об остаточном члене в центральной предельной теоремеP. Survila, Liekamojo nario centrinėje ribinėje teoremoje klausimu